Commissioning of GPU–Accelerated Monte Carlo Code FRED for Clinical Applications in Proton Therapy - Gajewski, Jan; Garbacz, Magdalena; Chang, Chih-Wei; Czerska, Katarzyna; Durante, Marco; Krah, Nils; Krzempek, Katarzyna; Kopeć, Renata; Lin, Liyong; Mojżeszek, Natalia; Patera, Vincenzo; Pawlik-Niedzwiecka, Monika; et al. (Frontiers in Physics, 2021)
We present commissioning and validation of Fred, a GPU-accelerated Monte Carlo (MC) code, for two proton beam therapy facilities of different beam line design: CCB (Krakow, IBA) and EMORY (Atlanta, Varian). We followed clinical acceptance tests required to admit the certified treatment planning system for clinical use. We implemented an automated and efficient procedure to build a parameter library characterizing the clinical proton pencil beam. Beam energy, energy spread, lateral propagation model, and a dosimetric calibration factor were parametrized based on measurements performed during the facility start-up. The Fred beam model was validated against commissioning and supplementary measurements performed with and without range shifter. We obtained (i) sub-millimeter agreement of Bragg peak shapes in water and lateral beam profiles in air and slab phantoms, (ii) <2% dose agreement for spread out Bragg peaks of different ranges (iii) average gamma index (2%/2mm) passing rate >95% for >1000 patient verification measurements using a 2D array of ionization chambers, (iv) GI passing rate >99% for 3D dose distributions computed with Fred and measured with an array of ionization chambers behind an anthropomorphic phantom. The results of example treatment planning study on >100 patients demonstrate that Fred simulations in patient CT enable an accurate prediction of dose distribution in patient and application of Fred as second patient quality assurance tool. Computation of a patient treatment in a CT using 10^4 protons per pencil beam took on average 2'30 min with tracking rate of 2.9x10^5 protons/s. Fred was successfully commissioned and validated against the clinical beam model showing that it could potentially be used in clinical routine. Thanks to high computational performance due to GPU-acceleration and an automated beam model implementation method, the application of Fred is possible for research or quality assurance purposes in most of the proton facilities.